Induction of nutritional mutants of Micrococcus glutamicus and their amino acid accumulation - Banik, A K; Majumdar, S K (Folia microbiologica, 1975)
Micrococcus glutamicus ATCC 13032, a glutamic acid-producing organism, was treated with 0.2M ethylmethane sulfonate, the auxotrophs isolated showing varied patterns of extracellular amino acids. Eighty auxotrophic strains were obtained, out of which 31 excreted 1.0-4.0 mg threonine per ml and all the auxotrophs required biotin for growth and production of the amino acid. Eleven auxotrophs produced 1.5 to 3.0 mg alanine per ml and these auxotrophs required amino acids for their growth. Other auxotrophs lost their excretion capacity in subsequent fermentation trials. Further mutation of the biotin-requiring auxotroph Micrococcus glutamicus EM with gamma rays resulted in the isolation of 89 auxotrophic strains, out of which 28 excreted threonine (up to 5.0 mg per ml) higher than the parent auxotroph. Exposure to X-rays yielded 97 auxotrophs, out of these 35 producing 1.0-3.0 mg methionine per ml and requiring biotin for growth and production of the amino acid. Other auxotrophs produced alanine (0.5 to 2.0 mg per ml) and threonine (2.0 to 3.3 mg per ml). Irradiation with gamma rays favoured the development of threonine producing auxotrophs while X-rays favoured methionine-producing auxotrophs.
Keywords: mutageny; methionin; Cobalt Radioisotopes; alanin; Radiation Genetics; Chromatography, Paper; radiační genetika; methansulfonáty; mutace; Mutagens; X-Rays; glutamáty; Threonine; Glutamates; počet buněk; kolorimetrie; rentgenové záření; Biotin; threonin; Mutation; Colorimetry; Micrococcus; Mesylates; fermentace; papírová chromatografie; Methionine; Fermentation; biotin; Cell Count; aminokyseliny; radioizotopy kobaltu; Alanine; Amino Acids